Improved chronostratigraphy for the Messel Formation (Hesse, Germany) provides insight into early to middle Eocene climate variability - Kaboth-Bahr, Stefanie; Schmitt, Clemens; Bauersachs, Thorsten; Zeeden, Christian; Wonik, Thomas; Schandl, Jonas; Lenz, Olaf; Wedmann, Sonja; Vasiliev, Iuliana; Mulch, Andreas; Lourens, Lucas; Pross, Jörg; et al. (Newsletters on stratigraphy, 2024)
Besides providing unique information on early mammal evolution, the UNESCO World Heritage Site “Messel Fossil Pit” (Hesse, Germany) yields detailed insight into short-term climate variability during the early to middle Eocene due to its annually laminated oil-shale sequence. Here, we constrain the chronostratigraphy of the sediments from the Messel paleolake to allow precise correlation with other marine and terrestrial archives from that time period. This study utilizes a suite of geochemical proxy data (gamma ray, total organic carbon and carbon isotopes of organic matter) obtained from a scientific drillcore (FB2001) from the depocenter of the Messel paleolake. The drillcore comprises the full succession of the lacustrine sediments of the Lower (LMF) and ~60% of the Middle Messel (MMF) Formations, including all marker beds that are used to stratigraphically correlate excavated fossil remains across the lake basin. Based on the proposed astronomical tuning, we infer that the LMF and MMF obtained in core FB2001 cover in total c. 840 kyr and were deposited between 48.06 Ma and 47.22 Ma. More specifically, our tuning yields a duration of c. 130 kyr and c. 430 kyr for the annually laminated oil shale of the LMF and MMF, respectively. Our results imply a slightly longer deposition of the LMF than previously proposed based on the same core. By contrast, the deposition of the MMF occurred over a slightly shorter time interval. As a result of our tuning approach, and considering the revision of a previously published 40Ar/39Ar age for the base of the LMF, the top of the MMF in core FB2001 has an age of 47.22 ± 0.21 Ma and is thus ~200 kyr younger than suggested previously. We also find that the average sedimentation rate (~20 cm/kyr) for the oil-shale intervals is slightly higher than previously estimated. In line with previously published palynological records our geochemical data point to a strongly variable climate during deposition of the LMF and MMF, with humidity changes being paced by orbital precession and eccentricity. The synchronicity of negative excursions in the organic matter-derived carbon-isotope signals for the LMF and MMF as presented in our study to those registered in quasi-global carbon-isotope compilations further corroborates the robustness of our age model. As these quasi-global carbon-isotope anomalies represent disturbances of the global carbon cycle and are often associated with abrupt warming events (“hyperthermals”), the organic-rich sediments recovered at Messel provide the opportunity to study the response of aquatic and terrestrial ecosystems to climate disturbances in unprecedented temporal resolution.
Online veröffentlicht: 31. Januar 2024
Gesehen am 25.06.2024